The Effectiveness of Counterpressure Implementation with Birth Ball in Reducing Labor Pain During the Active Phase of the First Stage in the Delivery Room of BaliMed Hospital Denpasar - Ni Putu Anggi Astuti; Ni Putu Yunita Sri Lestari; Ni Made Risna Sumawati (Jurnal Ilmiah Kebidanan (The Journal Of Midwifery), 2025)
Labor pain is a major concern for mothers during childbirth, particularly in the active phase of the first stage of labor. Effective and safe pain management is essential in midwifery care. One recommended non-pharmacological method is the combination of counterpressure techniques and the use of a birth ball. This study aimed to assess the effectiveness of implementing counterpressure with a birth ball in reducing labor pain at BaliMed Hospital Denpasar. A pre-experimental study with a one-group pretest-posttest design was conducted involving 30 mothers in the active phase of the first stage of labor, selected through accidental sampling. Pain intensity was measured using the Visual Analogue Scale (VAS) before and after the intervention. The results showed that the mean pain score decreased from 5.37 Â± 1.402 (moderate pain) to 3.60 Â± 1.329 (mild pain). The Wilcoxon Signed Rank Test indicated a statistically significant reduction in pain (Z = -4.869, p < 0.05). These findings suggest that counterpressure combined with birth ball therapy is effective in reducing labor pain. This method can be recommended as a simple, safe, cost-effective, and non-pharmacological alternative for managing pain during labor in clinical midwifery practice.